2018
DOI: 10.1002/jcph.1252
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacokinetic and Pharmacogenetic Analysis of Osteosarcoma Patients Treated With High‐Dose Methotrexate: Data From the OS2006/Sarcoma‐09 Trial

Abstract: Growing evidence suggests that polymorphisms of genes coding for transporters or enzymes may partially explain the large between subject variability reported for methotrexate (MTX) pharmacokinetics (PK). This prospective study aimed to develop a population PK-pharmacogenetic model to evaluate the part of between-subject variability due to single-nucleotide polymorphisms (SNPs) in transporters and enzyme genes implicated in MTX distribution and elimination. MTX concentrations and 54 SNPs (located in ABCB1, ABCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…The variant A allele was significantly associated with decreased MTX clearance in two studies [ 20 , 26 ], while the same directionality was observed in another study, without reaching significance [ 25 ], and no association was identified in the other three studies [ 23 , 24 , 27 ]. In addition, three SNPs (rs12505410, rs13120400, and rs13137622) were significantly associated with MTX PK in a single study [ 22 ]. Nevertheless, since this is the only article in which they were studied, additional studies would be needed to confirm those associations.…”
Section: Resultsmentioning
confidence: 99%
“…The variant A allele was significantly associated with decreased MTX clearance in two studies [ 20 , 26 ], while the same directionality was observed in another study, without reaching significance [ 25 ], and no association was identified in the other three studies [ 23 , 24 , 27 ]. In addition, three SNPs (rs12505410, rs13120400, and rs13137622) were significantly associated with MTX PK in a single study [ 22 ]. Nevertheless, since this is the only article in which they were studied, additional studies would be needed to confirm those associations.…”
Section: Resultsmentioning
confidence: 99%
“…Potential contributors to contrasting findings are differences in outcomes, different populations with different genetic backgrounds, and different HD-MTX treatment regimens (2 – 5 g/m² in hematological malignancies compared to 12 g/m² in osteosarcoma). A prospective candidate gene study investigating the relation of genetic variants and HD-MTX pharmacokinetics in osteosarcoma patients identified statistically significant associations between MTX clearance and variants in ABCG2 and UGT1A ( Lui et al., 2018 ). ABCG2 was not included in this study but the identified variant in UGT1A (rs4148324) was in high LD (r² > 0.90) with three variants in the present study (rs887829, rs111741722, rs10929302), but these variants showed no association with MTX 48 h plasma levels (using both an additive and dominant model, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We performed population PK analysis with a nonlinear mixed‐effects model implemented in NONMEM version VII 28 using a typical pediatric population PK modeling approach, similar to two recent HD MTX studies 29,30 . We chose the base model by comparing several compartment PK models with either a proportional residual error model or a combined additive and proportional residual error model, assuming lognormal distribution for random effects PK parameters.…”
Section: Methodsmentioning
confidence: 99%
“…27 Population PK analysis We performed population PK analysis with a nonlinear mixed-effects model implemented in NONMEM version VII 28 using a typical pediatric population PK modeling approach, similar to two recent HD MTX studies. 29,30 We chose the base model by comparing several compartment PK models with either a proportional residual error model or a combined additive and proportional residual error model, assuming lognormal distribution for random effects PK parameters. For estimations, we used the stochastic approximation expectation maximization, which was followed by importance sampling to obtain the object function and standard errors, because stochastic approximation expectation maximization could better handle more complex PK/ pharmacodynamic problems with many parameters than the first order conditional estimation with interaction.…”
Section: Treatment Details and Data Collectionmentioning
confidence: 99%